PENGARUH PARTISIPASI MASYARAKAT DESA HUTAN DALAM PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT (PHBM) TERHADAP KESEJAHTERAAN MASYARAKAT DESA HUTAN (STUDI KASUS DI BKPH KLUMO BANGSRI KABUPATEN JEPARA) - Naila Izzah; Edi Santosa; Hermini susiatiningsih (Journal of Politic and Government Studies, 2014)
AbstractThe essence of Forest Community Resource Management (FCRM) is giving space forest villagers to participate in the management of forest resources for the public welfare forest village. Thus of the theories that have been presented in the study show that the participation of forest villagers in FCRM have an influence on the public welfare forest villager The results of empirical tests on the effect of forest villagers participation BKPH Klumo Bangsri Jepara in Forest Community Resource Management (FCRM) on the welfare of forest villagers BKPH Klumo Bangsri Jepara shows that community participation in Forest Community Resource Management (FCRM) effect on the public welfare forest village. The results showed reject H0 and accept Ha which states